Development of a Mathematical Literacy Test Instrument Based on Local Wisdom in Blitar Raya for Fifth-Grade Elementary Students - Kirana, Rida Nanda; Surayanah, Surayanah; Mas’ula, Siti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to create and develop a mathematics literacy test instrument based on the local wisdom of Blitar Raya that is valid according to the opinions of material and instrument experts, and that is practical for educators and students in terms of validity, reliability, difficulty level, and the quality of distractors. The simplified eight-stage R&D model by Borg & Gall serves as the foundation for this research methodology. Data collection was obtained through unstructured observations, interviews, questionnaires for student needs analysis, student response surveys, and student feedback. The results of the expert validation of the instrument yielded 100% (very valid), and the expert validation of the content resulted in 93.75%. (very valid). In the small-scale test, 36 questions were found to be valid and 14 questions invalid, with 50 questions deemed reliable resulting in a reliability index of ri = 0.93. The difficulty index reached 0.61, categorized as moderate, and the discrimination power obtained an index of 0.60, categorized as good. Based on the practicality questionnaire results from teachers, it was 93.75%, and from students, it was 91.25%. In the large-scale test, 28 questions were valid and 8 invalid, with 36 questions reliable resulting in a reliability index of ri = 0.88. The difficulty index was 0.68, categorized as moderate, and the discrimination power obtained an index of 0.42, categorized as good. Based on the practicality questionnaire results from teachers, it was 90.62%, and from students, it was 94.6%.